Distribution of genes in the genome of Arabidopsis thaliana and its implications for the genome organization of plants - Barakat, Abdelali (The National Academy of Sciences, 1998)
Previous work has shown that, in the large genomes of three Gramineae [rice, maize, and barley: 415, 2,500, and 5,300 megabases (Mb), respectively] most genes are clustered in long DNA segments (collectively called the “gene space”) that represent a small fraction (12–24%) of nuclear DNA, cover a very narrow (0.8–1.6%) GC range, and are separated by vast expanses of gene-empty sequences. In the present work, we have analyzed the small (ca. 120 Mb) nuclear genome of Arabidopsis thaliana and shown that its organization is drastically different from that of the genomes of Gramineae. Indeed, (i) genes are distributed over about 85% of the main band of DNA in CsCl and cover an 8% GC range; (ii) ORFs are fairly evenly distributed in long (>50 kb) sequences from GenBank that amount to about 10 Mb; and (iii) the GC levels of protein-coding sequences (and of their third codon positions) are correlated with the GC levels of their flanking sequences. The different pattern of gene distribution of Arabidopsis compared with Gramineae appears to be because the genomes of the latter comprise (i) many large gene-empty regions separating gene clusters and (ii) abundant transposons in the intergenic sequences of gene clusters. Both sequences are absent or very scarce in the Arabidopsis genome. These observations provide a comparative view of angiosperm genome organization.